The Analysis of Students’ Learning Obstacles on the Fraction Addition Material for Five Graders of Elementary Schools - Irfan Fauzi; Didi Suryadi (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractVarious researchs have explained the students' difficulties in understanding fractions, so the researcher will analyze the student obstacle learning on fraction addition material. The approach used in this research is qualitative with the case study method. The subjects in this study were 5th grade students of Geger Kalong Girang 1-2 elementary school, Bandung City with a total of 29 students. Collecting data in this study using tests, interviews, and documentation. Data analysis uses data reduction, data display, and conclusion drawing/verification. The results of this study found that students experience 1) ontogenic obstacle caused by the students inablity to understand the picture presented so that they are not able to determine the amount of fractions; 2) epistemological obstacle caused by the inability of students to understand fractions as part of the whole and apply the wrong concept in operating fractions; and 3) didactical obstacle caused by informal teaching methods and presentation of teaching materials that did not pay attention to student involvement. This research can facilitates students in understanding fraction addition material and provides an overview to the teacher in making teaching materials and learning design about fraction addition based on learning obstacle.Keywords: learning obstacles, fraction addition, elementary school.Â AbstrakBerbagai penelitian telah menjelaskan terkait dengan kesulitan siswa dalam memahami pecahan, sehingga peneliti akan menganalisis learning obstacle siswa pada materi penjumlahan pecahan. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif dengan metode studi kasus. Subjek dalam penelitian ini adalah siswa kelas 5 SD Geger Kalong Girang 1-2 Kota Bandung dengan total 29 siswa. Pengumpulan data dilakukan dengan menggunakan tes, wawancara, dan dokumentasi. Adapun analisis data menggunakan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa siswa mengalami 1) ontogenic obstacle disebabkan karena ketidakmampuan siswa dalam memahami gambar yang disajikan, sehingga tidak mampu menentukan besaran pecahan pada gambar; 2) epistemological obstacle disebabkan karena ketidakmampuan siswa dalam memahami pecahan sebagai bagian dari keseluruhan dan menerapkan konsep yang salah dalam mengoperasikan pecahan; dan 3) didactical obstacle disebabkan karena cara mengajar guru yang bersifat informal dan penyajian bahan ajar yang kurang memperhatikan keterlibatan siswa. Penelitian ini dapat memfasilitasi siswa dalam memahami materi penjumlahan pecahan dan memberikan gambaran kepada guru dalam membuat bahan ajar dan desain pembelajaran penjumlahan pecahan berdasarkan learning obstacle.Kata kunci: learning obstacle, penjumlahan pecahan, sekolah dasar.Â